2011
DOI: 10.1007/s10750-010-0582-3
|View full text |Cite
|
Sign up to set email alerts
|

First feeding diet of young brown trout fry in a temperate area: disentangling constraints and food selection

Abstract: Diet composition of newly emerged brown trout fry in natural areas remains poorly known, and foraging abilities at this early stage, although presumably reduced, are still under discussion. We have studied gut content composition of brown trout fry in a temperate area (Galicia, NW Spain) and compared it to the benthic macroinvertebrate community. Small prey such as chironomid larvae and baetid nymphs were the most important food items for newborns, some of them still presenting yolk remnants. However, the posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 50 publications
4
36
0
Order By: Relevance
“…This study shows that the size-frequency distribution of gastrointestinal tracts was not identical to that in the benthos and drift samples. This supports the findings of Sánchez-Hernández et al (2011a) who found that the size-frequency distribution of potential prey items in the benthos was different to that of prey in the stomachs of brown trout. Our findings are in concordance with the observations of brown trout by Rincón and Lobón-Cerviá (1999), and prey-size selection is probably dependent of the characteristics of the size-frequency distribution of the available prey.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study shows that the size-frequency distribution of gastrointestinal tracts was not identical to that in the benthos and drift samples. This supports the findings of Sánchez-Hernández et al (2011a) who found that the size-frequency distribution of potential prey items in the benthos was different to that of prey in the stomachs of brown trout. Our findings are in concordance with the observations of brown trout by Rincón and Lobón-Cerviá (1999), and prey-size selection is probably dependent of the characteristics of the size-frequency distribution of the available prey.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the preference for Baetis spp. found in this study could also be related to site-specific prey accessibility as demonstrated by other researchers (Oscoz et al 2006, Johnson et al 2007, Leunda et al 2008, Sánchez-Hernández et al 2011a.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In addition, fishes can acquire foraging information from conspecifics (Reader et al 2003 and references therein), and as the predator acquires experience, the development of a search image can improve the ability to detect food, helping to account for the greater foraging efficiency observed in adults (Ware 1971;Morrison et al 1978). Handling ability of fishes is an important variable that may determine food selection (Cunha & Planas 1999;de Crespin de Billy & Usseglio-Polatera 2002;Sánchez-Hernández et al 2011a). In this sense, Oscoz et al (2006) stated that prey-handling costs in Cyprinidae species could be responsible for the observed inter-and intra-specific (size-related) changes in diet preferences.…”
Section: Discussionmentioning
confidence: 99%